2020
DOI: 10.1136/medethics-2019-105934
|View full text |Cite
|
Sign up to set email alerts
|

‘There is a lot of good in knowing, but there is also a lot of downs’: public views on ethical considerations in population genomic screening

Abstract: Publics are key stakeholders in population genomic screening and their perspectives on ethical considerations are relevant to programme design and policy making. Using semi-structured interviews, we explored social views and attitudes towards possible future provision of personalised genomic risk information to populations to inform prevention and/or early detection of relevant conditions. Participants were members of the public (n=30) who had received information on their personal genomic risk of melanoma as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Psychosocial and attitudinal barriers, such as anxiety and worry toward screening and the possibility for negative psychological and emotional impacts, were the most reported individual-level barriers across stakeholders, even though studies to date have demonstrated limited impacts on psychological and emotional outcomes with any adverse responses dissipating over time (Hietaranta-Luoma H.-L. et al, 2015;Hollands et al, 2016;Frieser et al, 2018;Smit et al, 2020). Of the studies that implemented screening programs, all screened for different disease states and half provided prescreen counseling mediated by a healthcare provider.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial and attitudinal barriers, such as anxiety and worry toward screening and the possibility for negative psychological and emotional impacts, were the most reported individual-level barriers across stakeholders, even though studies to date have demonstrated limited impacts on psychological and emotional outcomes with any adverse responses dissipating over time (Hietaranta-Luoma H.-L. et al, 2015;Hollands et al, 2016;Frieser et al, 2018;Smit et al, 2020). Of the studies that implemented screening programs, all screened for different disease states and half provided prescreen counseling mediated by a healthcare provider.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty articles were included. (Shaw and Bassi, 2001;Laskey et al, 2003;Toiviainen et al, 2003;Sanderson et al, 2004Sanderson et al, , 2017Allen et al, 2008;Borry et al, 2008;Neghina and Anghel, 2010;Haga et al, 2011;Hardie, 2011;Henneman et al, 2011;Nielsen and El-Sohemy, 2012;Nusbaum et al, 2013;Haga et al, 2014;Vassy et al, 2014;Hietaranta-Luoma et al, 2015;O'Neill et al, 2015;Shiloh et al, 2015;Godino et al, 2016;Nicholls et al, 2016;Sanderson et al, 2016;Vassy et al, 2017;Fenton et al, 2018;Hay et al, 2018;East et al, 2019;Rego et al, 2019;Rubinsak et al, 2019;Zoltick et al, 2019;Joshi et al, 2020;Smit et al, 2020).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…et al, 2019; Joshi et al, 2020;Smit et al, 2020) and one study did not record information about gender or sex (Joshi et al, 2020).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…To understand this problem, it is useful to bear in mind that the variants of a gene may or may not be pathogenic and that, if they are pathogenic, the severity of the illness may be difficult to determine. 19,201 In 21 explored social views and attitudes towards possible future provision of personalised genomic risk information to populations, using semi-structured interviews. The participants in their study did not identify clinical uncertainty, nor the possibility of false positives or false negatives as an ethical problem.…”
Section: Overdiagnosis Overtreatment and Incidental Findingsmentioning
confidence: 99%
“…In 21 explored social views and attitudes towards possible future provision of personalised genomic risk information to populations, using semi‐structured interviews. The participants in their study did not identify clinical uncertainty, nor the possibility of false positives or false negatives as an ethical problem.…”
Section: Overdiagnosis Overtreatment and Incidental Findingsmentioning
confidence: 99%